EVALUASI PROGRAM PENINGKATAN PRODUKSI KEDELAI DI KABUPATEN PURWOREJO PROVINSI JAWA TENGAH - Eko Susanto; Siti Hamidah; Sri Wuryani (Jurnal Dinamika Sosial Ekonomi, 2017)
Purworejo Regency is one of the soybean production centers in Central Java province. By 2015 the program has been implemented to increase production to support the achievement of Self Sufficiency soybean Soybean through Movement Implementation of Integrated Crop Management (GPPTT) and Area Development Plant (PAT). The purpose of this research is (1) analyze the achievements of the program implementation GPPTT and PAT; (2) analyze the soybean productivity improvement; and (3) identify the obstacles in the implementation of the program to improve soybean production in Purworejo. This study used survey methods, the research location is determined purponively in the District Pituruh an soybean production centers and implementing GPPTT widest GPPTT selected for Megulung Lor village for making the mechanization of the harvest and post-harvest, and soybean send. Jatirejo Farmers Group 2 was selected as the only group that has carried Farmers harvest and post-harvest mechanization. For non GPPTT been Desa Girigoado with consideration has been carrying out mechanizationand part-harvesi crop then have the Farmer Group Sri Dadi who do not carry our GPPTT. PAT program selected for the District Banyuurip, because it is a pioneer of soy PAT program, and the largest soybean planting areas. Sukowaten villages selected for the largest soybean planted area, Farmers Farmers Group Purwo been selected for a program implementing the most advanced soy PAT instinationally. Farmers samples was determined by census, each of 30 people for 2 and KT KT Jatirejo Sri Dadi, as well as 17 people from KT PurwoTani. The collection of data carried out by observation, interview and record keeping. Hypothesis testing using t test. The results showed that: (1) the realization of the planting area GPPTT program reached 64.85% while the PAT program reached 76 20%; (2) program and PAT GPPTT able to increase the productivity of soybean respectively by 82.66% and 42.81% of the target set; (3) the obstacles in the implementation of improvement programs soybean production in Purworejo, including the low usage of fertilizers, low productivity of soybean and soybean low selling prices PAT program Keywords: Soybean Production Enhancement Program, Productivity, Obstacle